Multispecies Outbreak of Verona Integron-Encoded Metallo-ß-Lactamase-Producing Multidrug-Resistant Bacteria Driven by a Promiscuous Incompatibility Group A/C2 Plasmid. (7th April 2020) - de Man, Tom J B; Yaffee, Anna Q; Zhu, Wenming; Batra, Dhwani; Alyanak, Efe; Rowe, Lori A; McAllister, Gillian; Moulton-Meissner, Heather; Boyd, Sandra; Flinchum, Andrea; Slayton, Rachel B; Hancock, Steven; et al.
Abstract: Background: Antibiotic resistance is often spread through bacterial populations via conjugative plasmids. However, plasmid transfer is not well recognized in clinical settings because of technical limitations, and health care–associated infections are usually caused by clonal transmission of a single pathogen. In 2015, multiple species of carbapenem-resistant Enterobacteriaceae (CRE), all producing a rare carbapenemase, were identified among patients in an intensive care unit. This observation suggested a large, previously unrecognized plasmid transmission chain and prompted our investigation. Methods: Electronic medical record reviews, infection control observations, and environmental sampling completed the epidemiologic outbreak investigation. A laboratory analysis, conducted on patient and environmental isolates, included long-read whole-genome sequencing to fully elucidate plasmid DNA structures. Bioinformatics analyses were applied to infer plasmid transmission chains and results were subsequently confirmed using plasmid conjugation experiments. Results: We identified 14 Verona integron-encoded metallo-ß-lactamase (VIM)-producing CRE in 12 patients, and 1 additional isolate was obtained from a patient room sink drain. Whole-genome sequencing identified the horizontal transfer of bla VIM-1, a rare carbapenem resistance mechanism in the United States, via a promiscuous incompatibility group A/C2 plasmid that spread among 5 bacterial species isolated from patients and the environment. Conclusions: This investigation represents the largest known outbreak of VIM-producing CRE in the United States to date, which comprises numerous bacterial species and strains. We present evidence of in-hospital plasmid transmission, as well as environmental contamination. Our findings demonstrate the potential for 2 types of hospital-acquired infection outbreaks: those due to clonal expansion and those due to the spread of conjugative plasmids encoding antibiotic resistance across species. Abstract : An outbreak investigation of Verona integron-encoded metallo-ß-lactamase–producing carbapenem-resistant Enterobacteriaceae (CRE) among 12 patients in an intensive care unit showed the horizontal spread of a rare carbapenem resistance mechanism via a promiscuous plasmid that spread among 5 CRE species.